PLAUSIBLE MECHANISMS BY WHICH ULTRASONIC WAVES AFFECT SEEDS - Pour, Mohammad Eteghadi; Hobbi, Mahsa; Ghasemi, Hadi; Nazari, Meisam (Plant Breeding and Seed Science, 2016)
To study the effect of sonication on the seed germination percentage and rate as well as the cell area of barley (Hordeum vulgare L.) a laboratorial experiment was performed as Completely Randomized Design (CRD) with 3 replications. The results indicated that the ultrasonic waves affect the seed germination, germination rate and cell area significantly (at 0.05). The results of the mean comparison tests (LSD, 0.05) showed that the highest germination percentage (100 %), germination rate and cell area (1370.71 µ2 ) is achieved through 15 minutes exposure to ultrasonic waves. It is concluded that weakening the seed’s cell wall rigidity by sonication results in more and faster water imbibition by the cells and improved germination.